Changes in structure and aroma release from starch–aroma systems upon α-amylase addition - Tietz, Melanie; Büttner, Andrea; Conde-Petit, Beatrice (European Food Research and Technology, 2008)
The influence of starch hydrolysis by α-amylase addition on structural properties and aroma release from starch–aroma systems was studied. A food model system composed of aqueous tapioca starch dispersion (4 g dry starch/100 g dispersion) and one aroma compound (menthone) was investigated. Structure breakdown and related changes in starch fraction (amylose) were measured by rheology and iodine-binding. Menthone release from the aroma-starch system in the headspace was followed by proton transfer reaction-mass spectrometry (PTR-MS) upon starch hydrolysis. A slightly higher viscosity was found for the starch–menthone system compared to the starch system without menthone upon α-amylase addition. One could hypothesise that menthone acts as a kind of nucleation agent for inducing structure build-up of starch segments, hindering starch degradation. An extensive aroma release from aroma–starch systems upon α-amylase addition was expected, but, instead, just a slight volatile increase was found after a starch hydrolysis time of 60 min. It is suggested that aroma release is the result of several superimposed effects ranging from viscosity effects to interactions between aroma compounds and starch degradation products.<br